Intermittent ischaemic arrest and cardioplegia in coronary artery surgery: coming full circle?. Issue 2 (August 1994) - Taggart, D P; Bhusari, S; Hopper, J; Kemp, M; Magee, P; Wright, J E; Walesby, R
Abstract : OBJECTIVE–To compare the cardioprotective efficacy of cold crystalloid cardioplegia and intermittent ischaemic arrest in patients undergoing elective coronary artery surgery. DESIGN–Prospective randomised trial. SETTING–London teaching hospital. SUBJECTS–20 patients with at least moderately good left ventricular function undergoing elective coronary artery surgery by one experienced surgeon and needing at least two bypass grafts. INTERVENTIONS–Patients were randomised to cold crystalloid cardioplegia or intermittent ischaemic arrest. MAIN OUTCOME MEASURES–The primary determinant of the efficacy of myocardial protection was serial measurement (before and at 1, 6, 24, and 72 hours after the end of cardiopulmonary bypass) of cardiac troponin T (cTnT), a highly sensitive and specific marker of myocardial damage. RESULTS–There was no significant difference in age, ejection fraction, number of grafts, bypass times, or cross clamp times between the two groups. One patient in the cardioplegia group had a perioperative infarct and was excluded from further study. In both groups there was a significant increase in cTnT, with peak concentrations being reached 6 hours after the end of cardiopulmonary bypass and remaining significantly high at 72 hours. At 6 hours the median (75% interquartile range) concentrations of cTnT were similar in both groups (1.8 (1.0-3.6) micrograms/l for cardioplegia v 1.9 (1.0-3.5) micrograms/l for intermittent ischaemic arrest). CONCLUSION–This trial shows that intermittent ischaemic arrest, even without systemic cooling or venting of the left ventricle, provides a similar level of myocardial protection to cardioplegia in patients with moderate left ventricular function and short ischaemic times.